2012
DOI: 10.4238/2012.april.10.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in local Brazilian horse lines using microsatellite markers

Abstract: ABSTRACT. Genetic variability at 11 microsatellite markers was analyzed in five naturalized/local Brazilian horse breeds or genetic groups. Blood samples were collected from 328 animals of the breeds Campeira (Santa Catarina State), Lavradeira (Roraima State), Pantaneira (Pantanal Mato-Grossense), Mangalarga Marchador (Minas Gerais State), as well as the genetic group Baixadeiro (Maranhão State), and the exotic breeds English Thoroughbred and Arab. We found significant genetic variability within evaluated micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…The average allelic diversity within the remnant Nordestino populations was similar to that observed in other horse breeds from Brazil and around the world (Sereno et al, 2008;Cothran et al, 2011;Conant et al, 2012;Silva et al 2012), in which similar microsatellite markers were used. High genetic diversity was observed in the remnant population of the Nordestino horse studied here, according to estimates of genetic composition (Table 1).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The average allelic diversity within the remnant Nordestino populations was similar to that observed in other horse breeds from Brazil and around the world (Sereno et al, 2008;Cothran et al, 2011;Conant et al, 2012;Silva et al 2012), in which similar microsatellite markers were used. High genetic diversity was observed in the remnant population of the Nordestino horse studied here, according to estimates of genetic composition (Table 1).…”
Section: Discussionmentioning
confidence: 53%
“…Nevertheless, the Nordestino horse population was in HWE. Silva et al (2012) found that populations of Campeiro, Lavradeiro, Pantaneiro, Baixadeiro, Mangalarga Marchador, Arab, and thoroughbred horse breeds were not in HWE. Those authors used 11 microsatellites, six of which were used in the present study (HMS3, HMS6, HMS7, HTG6, HTG7, and VHL20).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, for this reason, this estimation method is efficient for this breed and because, according to Silva et al (2012), there is a significant genetic proximity between the breed originally used to elaborate this method and the MM breed.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, analyses are more often conducted on non-coding sequences of nuclear DNA, e.g. microsatellites (Cañon et al, 2000;Silva et al, 2012;Xu et al, 2012) as well as on mitochondrial DNA (Vilà et al, 2001;Mirol et al, 2002;Kavar and Dovč, 2008).…”
Section: Introductionmentioning
confidence: 99%